(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The history of origin and Progression of Caryophyllaceae is connected with xerophytization of the Turgai flora, which was partly caused by the Oligocene and Miocene regressions of the Tethys, processes of orogenesis, and the Pleistocene glaciations. The Middle Asian and Mediterranean centers, which were connected to the Asia Minor and Balkan centers of diversity, played the main role in diversification of the family. Climatic and edaphic changes during the recent geological period (since the second part of the Holocene) promoted the formation of the new centers of diversity in the East European province, including the steppe zones of Ukraine (Black Sea coast area), in particular, the Pontic center. In these evolutionarily young centers, often weakly differentiated, morphologically endemic species were formed. The anthropogenic factors also played some role in further dispersal of some species of Caryophyllaceae of the Ukrainian flora, especially those originally confined to the Mediterranean region.